Synthesis, DFT Calculation, and Antimicrobial Studies of Novel Zn(II), Co(II), Cu(II), and Mn(II) Heteroleptic Complexes Containing Benzoylacetone and Dithiocarbamate - Anthony C. Ekennia; Damian C. Onwudiwe; Lukman O. Olasunkanmi; Aderoju A. Osowole; Eno E. Ebenso (Bioinorganic Chemistry and Applications)
Heteroleptic complexes of zinc(II), copper(II), manganese(II), and cobalt(II) of the types [MLL′(H2O)2]·nH2O and [MLL′]·nH2O have been synthesized using sodium N-methyl-N-phenyldithiocarbamate (L) and benzoylacetone (L′). The metal complexes were characterized by elemental analysis, electrical conductance, magnetic susceptibility, infrared (IR), and UV-visible spectroscopic studies. The electrical conductance measurements revealed the nonelectrolytic nature of the synthesized complexes. The results of the elemental analyses, magnetic susceptibility measurements, and electronic spectra inferred that the Zn(II) complex adopted a four-coordinate geometry while the Co(II), Cu(II), and Mn(II) complexes assumed octahedral geometries. The IR spectra showed that the metal ions coordinated with the ligands via the S- and O-donor atoms. The geometry, electronic, and thermodynamic parameters of the complexes were obtained from density functional theory (DFT) calculations. The spin density distributions, relative strength of H–bonds, and thermodynamic parameters revealed that the order of stability of the metal complexes is Mn < Co < Cu > Zn. The agar diffusion methods were used to study the antimicrobial activity of the complexes against two Gram positive bacteria (S. aureus and S. pneumoniae), one Gram negative bacterium (E. coli), and two fungi organisms (A. niger and A. candida) and the complexes showed a broad spectrum of activities against the microbes.